1982
DOI: 10.1002/apmc.1982.051080111
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical investigations into cellulosic materials, IV. Photosensitized free radical generation in cellulose acetate and oligosaccharide compounds

Abstract: ESR spectra of UV irradiated cellulose acetate, cellulose triacetate and oligosaccharide compounds (glucose, glucose pentaacetate, cellobiose, cellobiose octaacetate, maltose, maltotriose), both in photosensitized experiments, are recorded. These results extend the data obtained in the ESR investigation of cellulose and starch. They lead to a better insight into the nature of free radicals generated under UV light excitation. ZUSAMMENFASSUNG :Es wurden ESR-Spektren von photosensibilisiert-und nichtphotosensibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…The interpretation of the mechanism with the initial free-radical intermediates was confirmed by Merlin and Fouassier in 1982 who performed similar ESR studies on acetate films [56] and compared the resulting spectra with those from cellulose and similar monomeric reference substances.…”
Section: Degradation By Far Uv-lightmentioning
confidence: 75%
“…The interpretation of the mechanism with the initial free-radical intermediates was confirmed by Merlin and Fouassier in 1982 who performed similar ESR studies on acetate films [56] and compared the resulting spectra with those from cellulose and similar monomeric reference substances.…”
Section: Degradation By Far Uv-lightmentioning
confidence: 75%
“…These findings thus challenge the paradigm set by NOAA, governmental agencies, and advocacy groups that CDA-based materials persist in the ocean for decades. , The time line of CDA biodegradation is inherently subject to variation depending on a number of factors not considered in this study. For example, increased surface area:volume ratios through disintegration and physical abrasion or photochemical alterations of CDA chemical compositions likely shorten lifetimes. Moreover, considering other fates of CDA-C, such as incorporation into biomass or the production of metabolites, would shorten lifetimes. In contrast, the lifetimes of thicker CDA materials with lower surface area:volume ratios in colder, darker, and nutrient-limited waters are likely longer.…”
Section: Resultsmentioning
confidence: 99%
“…Although CA has good light stability, free radical generation in CA and photodegradation of CA under irradiation with ultraviolet have been reported in some literatures. [1][2][3] Hon has reported that ultraviolet exposure to CA fibers led to loss of sample weight and acetic acid content. 2 In our previous study using a xenon fadometer for light stability tests, however, CA films showed no detectable acetic acid generation or decrease in the molecular weight by photoirradiation for at least 28 days.…”
Section: Introductionmentioning
confidence: 99%
“…5,8 Merlin and Fouassier reported the generation of free radicals by irradiation of ultraviolet to cellulosic materials including CA with or without photosensitizers, and assumed that the glycosidic scission and the hydrogen abstraction occurred. 3,9 However, the effectiveness of photosensitizers for the photodegradation of cellulose derivatives including CA under ambient environment has not been demonstrated since the previous studies intended to realize the degradation of cellulosic polymers during the photo-graft polymerization on the polymers using photosensitizers.…”
Section: Introductionmentioning
confidence: 99%